Adherence to diabetic eye examination guidelines in Australia: the National Eye Health Survey. Issue 9 (15th May 2017) - Foreman, Joshua; Keel, Stuart; Xie, Jing; Van Wijngaarden, Peter; Taylor, Hugh R; Dirani, Mohamed
Abstract: Objective: To determine adherence to NHMRC eye examination guidelines for Indigenous and non‐Indigenous Australian people with diabetes. Design: Cross‐sectional survey using multistage, random cluster sampling. Setting: Thirty randomly selected geographic sites in the five mainland Australian states and the Northern Territory, stratified by remoteness. Participants: 1738 Indigenous Australians aged 40–92 years and 3098 non‐Indigenous Australians aged 50–98 years were recruited and examined between March 2015 and April 2016 according to a standardised protocol that included a questionnaire (administered by an interviewer) and a series of standard eye tests. Main outcome measures: Adherence rates to NHMRC eye examination guidelines; factors influencing adherence. Results: Adherence to screening recommendations was significantly greater among non‐Indigenous Australians (biennial screening; 77.5%) than Indigenous Australians (annual screening; 52.7%; P < 0.001). Greater adherence by non‐Indigenous Australians was associated with longer duration of diabetes (adjusted odds ratio [aOR], 1.19 per 5 years; P = 0.018), while increasing age was associated with poorer adherence in non‐Indigenous Australians (aOR, 0.70 per decade; P = 0.011). For Indigenous Australians, residing in inner regional areas (aOR, 1.66; P = 0.007) and being male (aOR, 1.46; P = 0.018) were significant factors positively associated with adherence. Conclusions: More than three‐quarters of non‐Indigenous Australians with diabetes and more than half of Indigenous Australians with diabetes adhere to the NHMRC eye examination guidelines. The discrepancy between the adherence rates may point to gaps in the provision or uptake of screening services in Indigenous communities, or a lack of awareness of the guidelines. A carefully integrated diabetic retinopathy screening service is needed, particularly in remote areas, to improve adherence rates.